Bovine Endometrial Epithelial Cells Scale Their Pro-inflammatory Response In vitro to Pathogenic Trueperella pyogenes Isolated from the Bovine Uterus in a Strain-Specific Manner - Ibrahim, Mohammad; Peter, Sarah; Wagener, Karen; Drillich, Marc; Ehling-Schulz, Monika; Einspanier, Ralf; Gabler, Christoph (Frontiers in Cellular and Infection Microbiology, 2017)
Among different bacteria colonizing the bovine uterus, Trueperella pyogenes is found to be associated with clinical endometritis (CE). The ability of cows to defend against T. pyogenes infections depends on the virulence of invading bacteria and on the host’s innate immunity. Therefore, to gain insights into bacterial factors contributing to the interplay of this host pathogen, two strains of T. pyogenes were included in this study: one strain (TP2) was isolated from the uterus of a postpartum dairy cow developing CE and a second strain (TP5) was isolated from a uterus of a healthy cow. The two strains were compared in terms of their metabolic fingerprints, growth rate, virulence gene transcription, and effect on bovine endometrial epithelial cells in vitro. In addition, the effect of the presence of peripheral blood mononuclear cells (PBMCs) on the response of endometrial epithelial cells was evaluated. TP2, the strain isolated from the diseased cow, showed a higher growth rate, expressed more virulence factors (cbpA, nanH, fimE, and fimG), and elicited a higher mRNA expression of pro-inflammatory factors (PTGS2, CXCL3, and IL8) in bovine endometrial epithelial cells compared with TP5, the strain isolated from the healthy cow. The presence of PBMCs amplified the mRNA expression of pro-inflammatory factors (PTGS2, CXCL3, IL1A, IL6, and IL8) in bovine endometrial epithelial cells co-cultured with live TP2 compared with untreated cells, especially as early as after 4 h. In conclusion, particular strain characteristics of T. pyogenes were found to be important for the development of CE. Furthermore, immune cells attracted to the site of infection might also play an important role in up-regulation of the pro-inflammatory response in the bovine uterus and thus significantly contribute to the host–pathogen interaction.